A Phase II Study of Biodegradable Stents Plus Palliative Radiotherapy in Oesophageal Cancer. Issue 5 (May 2021) - Maishman, T.; Sheikh, H.; Boger, P.; Kelly, J.; Cozens, K.; Bateman, A.; Davies, S.; Fay, M.; Sharland, D.; Jackson, A.
Abstract: Aims: Self-expanding metal stents provide rapid improvement of dysphagia in oesophageal cancer but are associated with complications. The aim of the present study was to test the effectiveness of an alternative treatment of combining biodegradable stents with radiotherapy. Materials and methods: A Simon two-stage single-arm prospective phase II trial design was used to determine the efficacy of biodegradable stents plus radiotherapy in patients with dysphagia caused by oesophagus cancer who were unsuitable for radical treatment. Fourteen patients were recruited and data from 12 were included in the final analyses. Results: Five of 12 patients met the primary end point: one stent-related patient death; four further interventions for dysphagia within 16 weeks of stenting (41.7%, 95% confidence interval 15.2–72.3%). The median time to a 10-point deterioration of quality of life was 2.7 weeks. Nine patients died within 52 weeks of registration. The median time to death from any cause was 15.0 weeks (95% confidence interval 9.6–not reached). Conclusion: The high re-intervention observed, which met the pre-defined early stopping criteria, meant that the suggested alternative treatment was not sufficiently effective to be considered for a larger scale trial design. Further work is needed to define the place of biodegradable stents in the management of malignant oesophageal strictures. Highlights: Biodegradable stents plus radiotherapy do not provide good palliation for oesophagus cancer. Biodegradable stents plus radiotherapy result in an unacceptably high re-intervention rate. Biodegradable stents plus radiotherapy result in initial oesophageal patency but poorer long-term outcomes. Pain is the most common adverse event after a biodegradable stent plus radiotherapy for oesophagus cancer.